2018
DOI: 10.1128/jvi.01842-17
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Terminus of Herpes Simplex Virus 1 Glycoprotein K (gK) Is Required for gB Binding to Akt, Release of Intracellular Calcium, and Fusion of the Viral Envelope with Plasma Membranes

Abstract: Previously, we have shown that the amino terminus of glycoprotein K (gK) binds to the amino terminus of gB and that deletion of the amino-terminal 38 amino acids of gK prevents herpes simplex virus 1 (HSV-1) infection of mouse trigeminal ganglia after ocular infection and virus entry into neuronal axons. Recently, it has been shown that gB binds to Akt during virus entry and induces Akt phosphorylation and intracellular calcium release. Proximity ligation and two-way immunoprecipitation assays using monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 96 publications
2
39
0
Order By: Relevance
“…Previously, we showed that gK is involved in facilitating fusion of the viral envelope with cellular membranes during virus entry [24][25][26][27][28]. Importantly, we showed that gK (31-68aa) deletion prevented the virus from entering axonal termini of neurons in culture and prevented retrograde virion transport after ocular infection [29]. UL20 physically interacts with gK and these interactions are necessary for intracellular transport and functions of both g K and UL20 [30].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previously, we showed that gK is involved in facilitating fusion of the viral envelope with cellular membranes during virus entry [24][25][26][27][28]. Importantly, we showed that gK (31-68aa) deletion prevented the virus from entering axonal termini of neurons in culture and prevented retrograde virion transport after ocular infection [29]. UL20 physically interacts with gK and these interactions are necessary for intracellular transport and functions of both g K and UL20 [30].…”
Section: Introductionmentioning
confidence: 80%
“…In contrast, VC2 exhibited superior protection and morbidity control against HSV-1(McKrae) lethal challenge. gk 31-68 deleted virus has been shown to defective in entering mouse neurons [42] by fusion of the viral envelope with cellular membranes [29], while it can enter into Vero cells via endocytosis and replicate in similar titers to the parental virus. This substantial difference in virus entry may induce significant downstream signaling responses that result in the observed differential efficacy in vaccine-induced protection.…”
Section: Discussionmentioning
confidence: 99%
“…Glycoprotein K (gK) is one of the 12 known glycoproteins encoded by the virus, and HSV-1 is covered by glycoproteins. gK is mainly involved in viral entry into corneal epithelial cells, membrane fusion, the intracellular spread of virions, and virion egress (86). Many studies support the viewpoint that gK plays important roles in viral replication and corneal scarring (6,87).…”
Section: The Role Of Glycoproteins In Hskmentioning
confidence: 98%
“…Previous studies have hinted at the ability of some of these proteins to influence entry pathways. For example, gK is thought to promote entry into neurons by fusion with the plasma membrane because deletion of the N terminus of gK switches entry to endocytosis (82). gC promotes efficient endocytic entry into CHO-HVEM and primary human keratinocytes (69).…”
Section: Discussionmentioning
confidence: 99%